1968
DOI: 10.1210/endo-83-4-691
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intrauterine Oxygen Tension in the Rat and Its Regulation by Ovarian Steroid Hormones

Abstract: Intrauterine oxygen tension was measured in vivo in the adult virgin rat using an oxygen microelectrode and amplifier assembly coupled with a continuous recording system. Intermittent fluctuations in pO« with varying degrees of regularity were observed. In the uterus of the intact rat the frequency of these alterations and level of average pO> were found to be determined primarily by the patency of the uterine arterioles which supply the capillary network in the endometrium. To only a minor degree did contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…A number of studies have demonstrated the advantages of hESC culture at reduced oxygen tensions, including reduced spontaneous differentiation, increased expression of pluripotency markers, fewer chromosomal aberrations and increased rates of proliferation [5,6,7,8,9,35] and low oxygen culture is thought to be more physiological [36,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the advantages of hESC culture at reduced oxygen tensions, including reduced spontaneous differentiation, increased expression of pluripotency markers, fewer chromosomal aberrations and increased rates of proliferation [5,6,7,8,9,35] and low oxygen culture is thought to be more physiological [36,37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, culture in lower O 2 levels helps maintain human ES cells in an undifferentiated state (134). Importantly, the oviducts and uterine horns of mammals exhibit oxygen tension in the 3% range, suggesting that fertilization and the early stages of embryonic development take place in physiologically hypoxic environments (135)(136)(137)(138).…”
Section: Metabolic Regulation Of Placental and Early Embryonic Develomentioning
confidence: 99%
“…At later stages of development, organ growth that precedes vascular development leads to hypoxic microenvironments (Maltepe and Simon, 1998;Mitchell and Yochim, 1968;Rodesch et al, 1992). During evolution, several organs have adapted to hypoxic developmental conditions and integrated hypoxia into their intrinsic genetic program as an external regulatory signal.…”
Section: Hypoxia and Developmentmentioning
confidence: 99%